Sulphur metabolism in Paracoccus denitrificans - Burnell, J (1975)
This thesis describes the pathway of sulphur metabolism in Paracoccus denitrificans (NCIB 89MJ-) The compounds involved in the sulphur metabolic pathway were determined in growth experiments (Chapter 2) and time-course and pulse-chase experiments, using radioactively labelled sulphate (Chapter 3). P. denitrificans is an assimilatory sulphate-reducing organism with a pathway of sulphate reduction involving in- organic intermediates. P. denitrificans can not utilise cysteine as a sole sulphur; cysteine inhibits amino acid metabolism at low concentrations and respiration at higher concentrations. Sulphate is taken up by P. denitrificans against a concentration gradient (Chapter 4.) . The mechanism of sulphate uptake was investigated using right side out and inside out membrane vesicles prepared from P. denitrificans. The uptake mechanism involves an uncoupler-sensitive transport mechanism driven either by respiration, or by a transmembrane pH gradient (alkaline inside). The active transport of sulphate was shown to be carrier-mediated, by its sensitivity to sulphydryl-group reagents. It is proposed that the sulphate carrier operates by a mechanism of electroneutral proton symport, and is capable of transporting sulphate in either direction across the plasma membrane (Chapter 5). ATP Sulphurylase, the initial enzyme involved in the activation of sulphate, was purified, and its kinetic and regulatory properties investigated (Chapter 6). ATP Sulphurylase activity was repressed by sulphite, sulphide and cysteine, and inhibited by sulphide. Accumulation of APS, the end-product of the ATP sulphurylase-catalysed reaction, could only be detected in the presence of inorganic pyrophosphatase, an enzyme which removed pyrophosphate, another end-product of sulphate activation. Inorganic pyrophosphatase was purified and its substrate specificity, kinetics and regulatory properties examined, in relation to its part in sulphate metabolism (Chapter 7). Inorganic pyrophosphatase is a constitutive enzyme which functions equally well with either Mg2+ or Co2+ as the cofactor. APS Kinase activity was detected in crude extracts of P. denitrificans. A new assay is described for measuring APS kinase activity (Chapter 8). APS Kinase was purified. Coupled enzyme assays, with purified ATP sulphurylase, inorganic pyrophosphatase and APS kinase, indicated that all three enzymes were necessary for the synthesis, and accumulation of PAPS (Chapter 8). No 3′-nucleotidase or enzyme "A" activity was detected. Serine transacetylase and O-acetyl serine sulphydrylase were purified and the kinetics and regulation of these two enzymes, investigated (Chapter 9). O-Acetyl serine lyase activity was detected in crude extracts of P. denitrificans, representing the first report of this enzyme in bacteria (Chapter 9). β-Cystathionase was purified and its kinetic and regulatory properties investigated; the unidirectionality of the cysteine to methionine pathway was confirmed (Chapter 10). Cysteinyl- and methionyl-tRNA synthetases were purified and the kinetics and regulation of these enzymes studied (Chapters 11 and 12 respectively). Both these enzymes possess different substrate specificities to the aminoacyl-tRNA synthetases from other organisms. Both enzymes appear to be constitutive. During this investigation of the sulphur metabolism of P. denitrificans, the substrate specificity of the different enzymes, to the selenium analogues of the respective sulphur-containing substrates, were investigated. Selenate competitively inhibits sulphate uptake and ATP sulphurylase, with respect to sulphate, but no APSe or PAPSe synthesis could be detected in the coupled enzyme assays (Chapters 7 and 8). Purified O-acetyl serine sulphydrylase catalysed the synthesis of selenocysteine from selenide and O-acetyl serine (Chapter 9). Both selenocysteine and selenomethionine are activated by the respective aminoacyl-tRNA synthetase (Chapters 11 and 12, respectively).